PERBEDAAN SELF EFFICACY PADA IBU MENYUSUI POST PARTUM NORMAL DAN POST SECTIO CAESAREA DI RSUD SEKARWANGI KABUPATEN SUKABUMI - Susilawati, Sofiea Febryaningsih (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2019)
The target for exclusive breastfeeding for infants is still lower than 80% of the national exclusive breastfeeding coverage target. Breastfeeding self-efficacy is the confident or belief possessed by mothers to breastfeed and be a predictor in exclusive breastfeeding for their babies, both in normal postpartum mothers and Post Sectio Caesarea. The purpose of this study was to determine the differences in self-efficacy in normal postpartum breastfeeding mothers with post sectio caesarea. This type of research uses a comparative study with a sample of 70 respondents and sampling with quota sampling. The questionnaire uses Breastfeeding Self Efficacy (BSE). Data analysis used an independent sample t-test. The results showed that the postpartum normal breastfeeding mothers obtained a mean of 60.48, while the postpartum cesarean breastfeeding mothers obtained a mean of 46.80. There is a difference in self-efficacy in normal postpartum breastfeeding mothers with post sectio caesarea with a p-value of 0,000. The results of the study can be a reference in increasing counseling to nursing mothers about the importance of exclusive breastfeeding in infants aged 0-6 months.